A review of "A New Vision of Value" – old wine, new bottle. Issue 4 (7th November 2016) - Barter, Nick
Abstract : Purpose: This paper is a review of KPMG's true value methodology. It highlights how a positive for the methodology is its advance of a systemic perspective, with the challenge being its furthering of an agenda of corporate centricity, where money is the mediator for societal decisions. Design/methodology/approach: This paper draws on existing literature to develop its arguments. Findings: The paper highlights how the true value methodology has merit for furthering a move towards the embrace of a more systemic thinking by business leaders; for example, how organisations are nested in society, not separate from society. However, the methodology is a cause for concern, because, for "true value" (ibid, p. 3) to be identified, albeit the notion of true value is one that stuns with its hubris, there is a need to monetise all exchanges and have corporations make societal well-being decisions based on monetary calculations as opposed to moral or ethical considerations. Thus, the methodology is advancing a corporate centric and narrowly defined perspective on what constitutes societal progress. Research limitations/implications: This paper is a review of the methodology with some critique and implications for management, leadership and culture discussed. Practical implications: The arguments presented highlight how the methodology furthers a particular perspective, and thus it should, like all tools, be used with an understanding of its limitations. Social implications: A key social implication brought forward in the paper is a corporate-centric perspective on societal progress. This corporate-centric perspective ensures that although a more systemic perspective is taken, society is viewed as a little more than a servant of the corporation. Originality/value: In drawing on existing literature, the originality lies in the combination of arguments brought together to realise the central claims.